HAK PENYANDANG DISABILITAS DALAM PERSPEKTIF HAM INTERNASIONAL DAN HAM NASIONAL - Aprilina Pawestri (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
Protection of the rights of persons with disabilities has shifted in its meaning, if persons with disabilities used to be viewed as "abnormal" conditions with discriminatory treatment and with "compassion" attitudes. Nowadays, the attention to persons with disabilities is a part of the fulfillment of human rights, because they are also creatures of God, with the same right, although they run their life with a special way. This condition is reinforced by the concrete steps of the international community by establishing various instruments to provide protection to persons with disabilities. At the national level, the government has ratified and also established national legal instruments to protect people with disabilities. There are Law Number 39 of 1999 which is supplemented by Law Number 19 of 2011. The replacement of Law Number 4 of 1997 with Law Number 8 of 2016 is a major step forward after the 1998 reform. It begins with the amendment of the Constitution of Republic of Indonesia on Article 28A-28J which specifically regulates human rights.Keywords: functions of the State, persons with disabilities, human rights